A meta-analysis of the feed intake and growth performance of broiler chickens challenged by bacteria - Remus, A. [UNESP]; Hauschild, L. [UNESP]; Andretta, I.; Kipper, M.; Lehnen, C. R.; Sakomura, N. K. [UNESP] (Oxford University Press, 2014)
The aim of this meta-analysis was to determine the effect of a bacterial immune challenge (Clostridium spp., Escherichia coli, and Salmonella spp.) on the ADFI, ADG, and nutrient partitioning (maintenance requirements and feed efficiency) of broiler chickens. The database used for the meta-analysis included 65 articles that were published between 1997 and 2012 concerning a total of 86,300 broilers and containing information on the feed intake, protein intake, methionine intake, and weight gain of broilers that were challenged with Clostridium spp., E. coli, or Salmonella spp. and were fed or not fed feed additives. The results of the ADFI and the ADG of the challenged broilers were transformed into values relative to those obtained in control broilers (Delta ADG and Delta ADFI). The meta-analysis involved 3 sequential analyses: graphical, correlation, and variance-covariance analysis. The results obtained for the birds that were challenged with Clostridium spp., E. coli, or Salmonella spp. indicated that the ADFI was reduced by 16, 7, and 9%, respectively, and the ADG was reduced by 40, 10, and 29%, respectively. When the results for the challenged birds that were treated or nontreated were compared, ADFI reductions of 26.0 and 26.5% and ADG reductions of 2.9 and 21.6% were observed, respectively. Regression analyses of the ADG as a function of the protein or methionine intake of the challenged birds suggested that nutrients were diverted to the immune system. The relationship between the Delta ADG and the Delta ADFI was quadratic in the challenged and nontreated or treated broilers, as well as for each disease. The intercept of the regression-based curves for the data from all of the challenges were different from zero and negative (-2.20, -0.70, and -3.37, respectively), indicating that all of the challenges increased the maintenance requirements. In general, this meta-analysis allowed for the quantification of the effects of bacteriological challenges on the maintenance and feed efficiency of broiler chickens, and the knowledge that was generated in this study is applicable to broiler nutrition and for modeling their nutritional requirements.
Keywords: meta-analytical study; Chicken; Protein; maintenance